Intergenerational Trauma and Aboriginal Women: Implications for Mental Health During Pregnancy - Roy, Amrita (First Peoples Child & Family Review, 2019)
Intergenerational trauma explains why populations subjected to long-term and mass trauma show a higher prevalence of disease, even several generations after the original events. Residential schools and other legacies of colonization continue to impact Aboriginal populations, who have higher rates of mental health concerns. Poor maternal mental health during pregnancy can have serious health consequences for the mother, the baby, and the whole family; these include impacting the cognitive, emotional, and behavioural development of children and youth. This paper has the following objectives: to define intergenerational trauma and contextualize it in understanding the mental health of pregnant and parenting Aboriginal women; to summarize individual-level and population-level approaches to promoting mental health and examine their congruence with the needs of Aboriginal populations; and to discuss the importance of targeting intergenerational trauma in both individual-level and population-level interventions for pregnant Aboriginal women. Various scholars have suggested that healing from intergenerational trauma is best achieved through a combination of mainstream psychotherapies and culturally-entrenched healing practices, conducted in culturally safe settings. Pregnancy has been argued to be a particularly meaningful intervention point to break the cycle of intergenerational trauma transmission. Given the importance of pregnant women’s mental health to both maternal and child health outcomes, including mental health trajectories for children and youth, it is clear that interventions, programs, and services for pregnant Aboriginal women need to be designed to explicitly facilitate healing from intergenerational trauma. In this regard, further empirical research on intergenerational trauma and on healing are warranted, to permit an evidence-based approach.